2008
DOI: 10.1080/17290376.2008.9724903
|View full text |Cite
|
Sign up to set email alerts
|

Establishing support groups for HIV-infected women: Using experiences to develop guiding principles for project implementation

Abstract: HIV-infected women need support to deal with their diagnosis as well as with the stigma attached to HIV. As part of their practical training, Master's-level psychology students negotiated with the staff of four clinics in townships in Tshwane, South Africa, to establish support groups for HIV+ women and offered to assist them in facilitating the groups. This study aimed to understand why the implementation of groups was successful in one clinic and not other clinics. The student reports on their experiences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In this study, unemployed participants also cited time as a barrier; their home schedule and health status did not allow them to attend support groups. Time was found to be a barrier to attending support group meetings in previous studies [6,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, unemployed participants also cited time as a barrier; their home schedule and health status did not allow them to attend support groups. Time was found to be a barrier to attending support group meetings in previous studies [6,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction with other HIV positive people is an essential component in the success of support groups and creates a sense of belonging among mutually empathetic members [5,6]. Participation in support groups also offers benefits of improved adherence to medication, decreased risk behavior for reinfection such as safer sex practices, condom use, and HIV status disclosure [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study found that groups can provide individuals with a nonstigmatizing atmosphere in which to gain information, share experiences, and learn from one another (Visser & Mundell, 2008). Support groups can help to renew hope, contribute to social reintegration, and help people feel they are taking control of their lives (Visser & Mundell, 2008).…”
Section: How Stigma Affects Prevention Interventionsmentioning
confidence: 97%